Identification of Mathematical Models of Heat Transfer of HTSC Coils. 2. Algorithm for Solving IHP and the Results of Experimental Data Processing - Alifanov, O. M.; Budnik, S. A.; Vikulov, A. G.; Nenarokomov, A. V.; Titov, D. M.; Morzhukhina, A. V.; Il’in, V. V. (Journal of engineering physics and thermophysics, 2023)
The presented work is a continuation of the development of a computational and experimental method for determining the thermophysical characteristics (TPC) of the stator coils of a generator operating with the use of the phenomenon of high-temperature superconductivity (HTSC). The paper considers algorithms for identifying heat transfer models in the composite material of the stator coil winding. Using the discovered thermophysical properties, it is planned to study the electrothermal interaction in a high-temperature superconductor before its transition to a superconducting state. There is a significant variety of methods for solving the problems of identifying mathematical models of heat transfer, in particular, of determining the thermophysical characteristics of composite materials. As a result of the analysis of alternative methods for solving the identification problem, the iterative regularization method is used in this work.